The Relationship between Emotional Intelligence and Student Learning Achievement at MA Bahrul 'Ulum Tambakberas Jombang - Nur, Luluk Choirun Nisak; Shaleh, Shaleh; Rohmah, Hidayatur (Universitas KH. A. Wahab Hasbullah, 2023)
There is another factor that is no less important in achieving success than intellectual intelligence, that factor is emotional intelligence. A person's rationality is actually guided and can even be controlled by emotions. People with good emotional skills are likely to be happy and successful in life, because they can know and deal with their feelings well so that they can focus on work and not be stressed, and they are able to read and deal effectively with other people's emotions. The purpose of this study is to determine the level and results of emotional intelligence and students' learning achievement, as well as to analyze the relationship between emotional intelligence and students' learning achievement at MA Bahrul 'Ulum Tambakberas Jombang. This type of research is descriptive and inferential quantitative research with 92 respondents. Data were obtained through questionnaire instruments and documentation formats. This study resulted in findings that the emotional intelligence of students is in the high category with a presentation of 76.1%, student learning achievement is in the good category with a percentage of 97.8% and there is a significant relationship between emotional intelligence and student learning achievement at MA Bahrul 'Ulum Tambakberas Jombang.